The role of the temporal pole in modulating primitive auditory memory. (21st April 2016) - Liu, Zhiliang; Wang, Qian; You, Yu; Yin, Peng; Ding, Hu; Bao, Xiaohan; Yang, Pengcheng; Lu, Hao; Gao, Yayue; Li, Liang
Highlights: A break in interaural correlation is used to study primitive auditory memory (PAM). Anterior temporal lobectomy (ATL) in humans does not abolish the PAM. Unilateral ATL shortens the temporal preservation of PAM of contralateral sounds. The temporal pole top-down modulates PAM of sounds entering the contralateral ear. Abstract: Primitive auditory memory (PAM), which is recognized as the early point in the chain of the transient auditory memory system, faithfully maintains raw acoustic fine-structure signals for up to 20–30 milliseconds. The neural mechanisms underlying PAM have not been reported in the literature. Previous anatomical, brain-imaging, and neurophysiological studies have suggested that the temporal pole (TP), part of the parahippocampal region in the transitional area between perirhinal cortex and superior/inferior temporal gyri, is involved in auditory memories. This study investigated whether the TP plays a role in mediating/modulating PAM. The longest interaural interval (the interaural-delay threshold) for detecting a break in interaural correlation (BIC) embedded in interaurally correlated wideband noises was used to indicate the temporal preservation of PAM and examined in both healthy listeners and patients receiving unilateral anterior temporal lobectomy (ATL, centered on the TP) for treating their temporal lobe epilepsy (TLE). The results showed that patients with ATL were still able to detect the BIC even when an interaural interval was introduced, regardless of which ear was the leading one. However, in patient participants, the group-mean interaural-delay threshold for detecting the BIC under the contralateral-ear-leading (relative to the side of ATL) condition was significantly shorter than that under the ipsilateral-ear-leading condition. The results suggest that although the TP is not essential for integrating binaural signals and mediating the PAM, it plays a role in top-down modulating the PAM of raw acoustic fine-structure signals from the contralateral ear.